Early Thymectomy Is Associated With Long-Term Impairment of the Immune System: A Systematic Review - Cavalcanti, Nara Vasconcelos; Palmeira, Patrícia; Jatene, Marcelo Biscegli; de Barros Dorna, Mayra; Carneiro-Sampaio, Magda (Frontiers in Immunology, 2021)
Background and aims: Congenital heart diseases (CHD) are diagnosed in approximately 9 in 1,000 newborns, and early cardiac corrective surgery often requires partial or complete thymectomy. As long-term impact of early thymectomy on the subsequent development of the immune system in humans has not been completely elucidated, the present study aimed to evaluate the effects of thymus removal in the functional capacity of the immune system after different periods of time. Methods: A systematic review of the literature was performed using MEDLINE, EMBASE, LILACS and Scopus. The inclusion criteria were original studies that analyzed any component of the immune system in CHD patients who had undergone thymectomy during cardiac surgery in the first years of life. The results were evaluated for quality of evidence. Results: 23 studies were selected and demonstrated that patients thymectomized in the first years of life have a trend to important alterations in T cell compartment such as fewer total T cells, CD4+, CD8+, naïve and CD31+ T cells, lower TRECs, a decreased diversity of the TCR repertoire and higher peripheral proliferation (increased Ki-67 expression) when compared to controls. However, numbers of memory T cells and Treg cells were divergent across the selected studies. Conclusions: Early thymectomy, either partial or complete, may be associated with reduction of many T cell subpopulations and TCR diversity and such alterations can persist on long-term follow-up. Alternative solutions should be studied, either in the operative technique with partial preservation of the thymus or through the autograft of fragments of the gland.